REGIONAL PLANNING STRATEGY TO SUPPORT THE DEVELOPMENT OF CULTURE-BASED TOURISM AREAS: A CASE STUDY IN SILALAHISABUNGAN DISTRICT, DAIRI REGENCY - Sihar Sinurat; Abdiyanto; Cut Nuraini (PT. Radja Intercontinental Publishing, 2025)
Silalahisabungan District in Dairi Regency has great potential for development as a culture-based tourism area. The natural beauty of the Lake Toba coast, the richness of local traditions, and cultural sites make this area unique and attractive. However, the development of this area faces challenges such as a lack of supporting infrastructure, low community involvement, and suboptimal policies and governance. This study aims to analyze the existing potential and challenges and formulate an appropriate regional planning strategy to support the development of culture-based tourism in Silalahisabungan District. The research method used a qualitative approach with data collection techniques such as interviews, surveys, and documentation. Data analysis was conducted using the SWOT method to formulate an effective strategy. The results indicate that recommended strategies include the development of supporting infrastructure, tourism promotion and marketing, local community and stakeholder involvement, environmental and cultural preservation, and the provision of attractive cultural attractions. In addition, the preservation of local cultural wisdom such as regional arts and cultural sites is a primary focus in the development of this area. A sustainable regional planning strategy not only encourages tourism development but also improves the welfare of local communities and maintains cultural and environmental authenticity. With proper implementation, Silalahisabungan District can become a superior and globally competitive culture-based tourism destination.